2022
DOI: 10.1155/2022/2178579
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Effect of Classroom Reform of English Literature on the Theme of Environmental Protection in Universities Based on Artificial Intelligence Technology

Abstract: Under the current theme of environmental protection, the effect of English literature classroom teaching reform cannot be analyzed qualitatively. Based on BP neural network, we present an analytical model of the impact of College English Literature Classroom Teaching Reform on environmental protection based on artificial intelligence technology. We analyze the teaching reform of English literature classrooms with the theme of environmental protection under artificial intelligence technology and explore the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One of the major challenges is that the development and application of AI in HLI lack an all-inclusive public policy. In most countries, AI lacks strong policy support despite its incredible potential for enhancing higher education (Li, 2022). The executive boards of Figure 2 (Microsoft Research, 2021): The Future of Higher Education 15 HLI lack adequate financial and ethical support to enable them to focus on using AI to enhance student performance.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…One of the major challenges is that the development and application of AI in HLI lack an all-inclusive public policy. In most countries, AI lacks strong policy support despite its incredible potential for enhancing higher education (Li, 2022). The executive boards of Figure 2 (Microsoft Research, 2021): The Future of Higher Education 15 HLI lack adequate financial and ethical support to enable them to focus on using AI to enhance student performance.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%